Family Business Formalization in South Eastern Nigeria: The Role of Intra-Industry Network - Agbim, Kenneth Chukwujioke (International Journal of Small and Medium Enterprises, 2018)
In most developing countries, majority of the family businesses are started with the support of networks on a small scale in the informal sector because the families and entrepreneurs are poor. Moreover, in areas where they are actively involved in networks, the benefits of such network relationships are rarely harnessed. In South Eastern Nigeria, the state of informality among family businesses has become a source of worry to both the State governments and owner-managers of family businesses. This is coming on the heels of the country’s economic recession and the need for the governments to increase their internally generated revenue. And the quest by the family business owner-managers to evade tax so as to increase their income. This is evident from the increasing number of family businesses that are operating outside government system of regulation in the zone. Based on these scenarios this study seeks to assess the effect of intra-industry network on family business formalization in South Eastern Nigeria. Survey design was adopted for the study. The study data were generated through questionnaire and analyzed using linear regression. The results show that intra-industry network significantly and positively affect family business formalization. The researcher recommends encouraging family business owner-managers to be interconnected with other founder/CEOs or descendant/CEOs and family firm employees within the same industry for the mutual benefit of acquiring and sharing information and knowledge that will facilitate the formalization process of their family businesses.